4-(Benzoxazol-2-yl)phenyl 3-((3-Chloro-1,4-Naphthoquinon-2-yl)amino)phenyl Sulfate - Nadezhda V. Danilenko; Mariia O. Lutsuk; Andrei I. Khlebnikov (Molbank)
New 4-(benzoxazol-2-yl)phenyl 3-((3-chloro-1,4-naphthoquinon-2-yl)amino)phenyl sulfate was synthesized via the SuFEx click reaction between fluorosulfate-containing 1,4-naphthoquinone and 2-(4-hydroxyphenyl)benzoxazole. 1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU) was used as an organic base, while triethylamine was inactive in this reaction.